Improvement of indoor thermal environments through green refurbishment - Lee, Kyu In (Sustainability (Switzerland), 2020)
This study investigates the performance of the "green refurbishment" of existing buildings. Two ordinary rooms in an existing building were chosen for examination. Refurbishment measures such as additional insulation, high-performance glazing, and air-tightening were applied to the control room. Temperature and electricity use were monitored to identify heating performance in winter and then compared with a baseline. The results of the field tests showed that green refurbishment significantly improved heating performance. Lowered heating load and electricity use with increased airtightness were also verified through building performance simulations. The empirical investigation suggests a predictive model to obtain indoor minimum temperatures as a function of outdoor temperature swings.
Keywords: Building performance; Energy simulation; Green refurbishment; Green retrofit; Monitoring experiment